Deflexão de vigas com carga variável - Silva, Álvaro Felipe Agostinho da (Universidade Federal Rural do Semi-Árido, 2018)
The bending of beams is one of the subjects related to engineering, with the different strategies in their problems. In general, the problem is presented with constant load along the longitudinal axis of the beam, and this work will make a study of flexions with variable loads with respect to the axis. Through a bibliographical analysis, a study was made on the behavior of the elastic lines having as main approach a linear structure, the beam, when being subjected to a load that is varying. By means of equations of equilibrium, compatibility of deformations and constitutive model of the material comes to non-homogeneous differential equations that will be solved. And after the application of contour conditions, the results are graphically illustrated.
Monografia
Keywords: Vigas; Beams; Equações Diferenciais; Differential Equations; Linha Elástica; Elastic Line; Flexão; Flexion; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA